Ethnography Study: The Power of Agent in Determining the Cost of Production from Indonesia Heritage Product - RIDWAN, Ridwan; INDRIASARI, Rahayu; JAMALUDDIN, Jamaluddin; TOTANAN, Chalarce; PARWATI, Ni Made Suwitri (Journal of Governance, Taxation and Auditing, 2023)
Currently, business development in Indonesia is very fast after the COVID-19 pandemic. The pandemic and recession have many experiences. A person with a business must improve the efficiency and effectiveness of his business production process to be competitive. Business competition not only requires business owners to produce goods but also how producers are right in calculating the cost of production of the goods they produce. When business owners know how much they spend to produce their products, they will be easier to manage and decide how much the product's price is and the profit from every product. The concept of cost is one line with efficiency practice. That means cost efficiency may give the entities more opportunity to up their profit. This study aims to find the practice of determining the Cost of Production of Donggala buya sabbe as a local heritage by home industries in Central Sulawesi. The research method uses an ethnographic approach with an interpretive paradigm. The study found that determining the cost of production on buya sabbe woven fabrics by weavers was based on three theme dimensions: customer custom tastes, expertise factors, and role division. Of these three dimensions, in the ethnographic record, one defining the value of the cost of production is the power of collectors as agents and the motive of the weavers to continue working not because they want to preserve heritage culture but because of economic motives.